2022
DOI: 10.3389/fneur.2022.1026221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term spinal cord stimulation on patients with prolonged disorder of consciousness: A pilot study

Abstract: BackgroundSpinal cord stimulation (SCS) can improve the level of awareness of prolonged disorder of consciousness (pDOC), but its application is restricted due to damage of invasive operation. Short-term spinal cord stimulation (st-SCS) in a minimally invasive manner will better balance the benefits and risks.ObjectivesThis study focuses on the safety and efficacy of st-SCS for pDOC and reveals the modulation characteristics of different frequencies of SCS.Methods31 patients received 2-week st-SCS treatment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
(26 reference statements)
2
14
0
Order By: Relevance
“…Furthermore, clinical data such as age, sex, and history of the disease are important for clinical treatment (42). There was no significant difference between the efficacy and inefficacy groups in terms of age, sex, hypertension, or MISPT history in our study; this result is similar to that reported in the literature (33). In addition, a subdivision of the MCS diagnosis did not reveal any significant differences between the two groups, contrary to previous research.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Furthermore, clinical data such as age, sex, and history of the disease are important for clinical treatment (42). There was no significant difference between the efficacy and inefficacy groups in terms of age, sex, hypertension, or MISPT history in our study; this result is similar to that reported in the literature (33). In addition, a subdivision of the MCS diagnosis did not reveal any significant differences between the two groups, contrary to previous research.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, st-SCS stimulation strategies were drawn from others reported for DOC. According to previous reports, the CRS-R score significantly increased after 2 weeks of DOC treatment at 70 Hz (33,34); we selected this frequency for this study. According to previous studies, neuronal fatigue or damage was reduced if the stimulation time was shorter than the off-stimulation time (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhuang et al conducted a pilot study to investigate the effects of short-term SCS. The results revealed that short-term SCS at 5 Hz could significantly improve CRS-R scores after 2 weeks, while stimulation at 70 Hz showed statistically significant effects after 1 week [46 ▪ ]. Those results suggest that higher SCS frequencies may achieve better clinical outcomes because of increased CBF.…”
Section: Resultsmentioning
confidence: 77%